Penerapan Media Quizizz Pada Materi Teks Biografi Kelas X SMA Negeri 11 Semarang - Puji Rahayu, Ika; Handayani, Sri; Umaya, Nazla Maharani (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Education aims to create a learning environment that allows students to develop their potential actively and effectively. In this context, the use of technology in learning becomes increasingly important to face the challenges of digital-based education. The Quizizz application, which is a quiz game-based educational platform, offers innovative solutions to improve learning outcomes through an interactive multimedia approach. This research examines the use of Quizizz in learning biographical text material in class X5 of SMA Negeri 11 Semarang. Quizizz's qualitative descriptive method in increasing student involvement and understanding. The research results show that Quizizz not only provides an interesting and interactive learning experience, but also provides instant feedback and analytical data to evaluate student progress. With these features, Quizizz can motivate students, make assignments and homework easier, and encourage creativity in teaching. This research underlines that Quizizz media can be an effective tool for improving learning outcomes and making the learning experience more enjoyable